Elachista adelpha sp. n., E. coeneni titanella ssp. n, and other Elachistidae (Lepidoptera) from North Caucasus - Kaila, Lauri; Jalava, Jukka (Entomologica Fennica, 1994)
Five species belonging to the Elachistidae are reported from North Caucasus. Three of these species have previously been known only from the mountains of Central and Southeastern Europe. New taxa: Elachista adelpha sp. n. and Elachista coeneni titanella ssp. n.